Analisis Persepsi Mahasiswa terhadap Lingkungan Pembelajaran di Laboratorium Kimia pada Mata Kuliah Praktikum Kimia Organik - Suryani, Elma; Hayatunnisa; Lisdiana, Hayyun; Sriyuliani, Rifa (Jurnal Riset Pendidikan Kimia (JRPK), 2024)
This research aims to analyze students' perceptions of the learning environment in the chemistry laboratory in the organic chemistry practicum course. The subjects of this research were class B Chemistry Education students, 36 students from the class of 2021 and 31 students from the class of 2022. The research was conducted based on the differences in the class of chemistry B students in carrying out organic chemistry practicum. The instrument used in this research was the CLEI (Chemistry Laboratory Environment Inventory) instrument. The CLEI (Chemistry Laboratory Environment Inventory) instrument is an instrument used to evaluate the chemical laboratory environment. The CLEI instrument is divided into 5 dimensions, namely student cohesiveness, open-endedness, integration, rule clarity, and material environment. Data collection techniques in this research used questionnaires and interviews. The method used in this research is qualitative research. The results of this research show that there is interaction between students such as working together and helping each other in groups, there is the opportunity for students to design practical experiments, there is integration between theory in class and practice carried out during practicum, there are formal rules to regulate and supervise the course of practicum, and completeness of tools and materials is still not good with there are still tools that function less well.